2012
DOI: 10.1080/19371918.2012.630965
|View full text |Cite
|
Sign up to set email alerts
|

Mothers in Prison: Maintaining Connections with Children

Abstract: The significant increase in the number of incarcerated women ensures that many children must live without their mothers for some period of time. Women in prison were interviewed about their efforts to maintain relationships with their children. Mail and telephone contacts were more frequent than actual visits. Almost one half of mothers had never received a visit from their children. This article identifies challenges to the development and maintenance of contact between incarcerated mothers and their children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 30 publications
0
72
0
4
Order By: Relevance
“…Study participants identified numerous social and economic barriers to reentry that can affect health and stability (7), a greater number than identified in most prison studies (2,3). When organized into domains, these barriers reflected the proximal and intermediate social determinants of health recognized by the World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
“…Study participants identified numerous social and economic barriers to reentry that can affect health and stability (7), a greater number than identified in most prison studies (2,3). When organized into domains, these barriers reflected the proximal and intermediate social determinants of health recognized by the World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
“…Une fois incarcérées, les mères n'ont que peu de possibilités de maintenir des liens avec leurs enfants. Les visites 4 , les appels téléphoniques et les lettres sont les seules occasions où elles peuvent exercer leur rôle et tenter d'assumer leurs responsabilités parentales (Arditti et Few, 2006 ;Blanchard, 2002 ;Mignon et Ransford, 2012). Certaines mères tentent alors de maintenir leur lien maternel auprès de leurs enfants, notamment en s'informant de leur cheminement scolaire et en cherchant à s'impliquer dans la prise de décision les concernant (Celinska et Siegel, 2010).…”
Section: êTre Mère De L'intérieurunclassified
“…McGrath () focused on the issue of parole serving more of a function of surveillance and control rather than being service‐oriented. She believes that the strengthening of family networks would be crucial in the transition back into the community, yet, parole supervision does not operate on this type of system (Duwe and Clark ; McGrath ; Mignon and Ransford ). Although the findings included males and females, some studies suggest that roughly two thirds of released inmates will be rearrested within 3 years upon release (Duwe and Clark ).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Stigmatization of children of incarcerated parents has been noted by both school officials and caregivers (Arditti 2012). The incarceration of mothers can and does have serious implications for many children (Huebner and Gustafson 2007;Mignon and Ransford 2012).…”
Section: The Role Of Relationshipsmentioning
confidence: 99%